Peran Komunitas “Menace Space” Untuk Eksistensi Band Indiependent di Kota Padang - Riswa Jiyan Dusa (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to determine the extent of the role of the Menace Space music community in supporting the development and promoting the existence of independent bands in Padang City. This research is qualitative in nature. The main instruments used in this study were the researchers themselves, supported by additional instruments such as writing tools, a recorder, and a camera. Data collection techniques were carried out through observation, interviews, literature review, and documentation. The steps for analyzing the data include data collection, data description, and drawing conclusions. The results of the study show that the contributions of the Menace Space community to the existence of independent bands in Padang City include financial and material support, promotion and marketing, event and gig organization, providing feedback and input, creative collaboration and support, as well as building a loyal fan base. Efforts made by Menace Space to promote independent bands include providing creative space, organizing events and gigs, offering networks and relationships, promotion and publicity, building a local music ecosystem, and providing inspiration and motivation.